(untitled) (The Review of Diabetic Studies, 2025)
The current project is focused on emergency medical training that all anaesthetists have to achieve. This is the ACCS (Acute Common Care Stem in Appropriate Common Care Training) programme for consultants in anaesthesia and intensive care who have completed a specific level of training. Within 111 training, one of the primary goals is to achieve early and accurate identification of life- and limb-threatening emergencies. This can be very challenging and stressful for the clinician; therefore, a new approach to the treatment of the psychological and emotional needs of the clinician involved in an emergency is valuable. ACCS trainees are subject to significant levels of stress, and these issues will be more significant when dealing with emergencies in a variety of settings. These trainees often have to deal with life and limb-threatening emergencies, significant trauma, and complicated medical conditions, which are very emotionally charged situations. During the ACCS training, these trainees may experience training in 111 emergency medicine through various shifts and scenarios, and a significant number of them may be exposed to real-life scenarios where they will need to manage major medical emergencies. These trainees have found certain situations and scenarios in dealing with emergencies to be unexpectedly stressful because they brought back emotions or memories of a real situation that had gone wrong. A novel approach to taking a debrief for those who found the situation stressful and using CBT passed by a clinical psychologist to change those memories would be significantly easier in a simulated scenario compared to real life. Thus, having a systematic approach to identify such situations, the level of psychological stress, and how it impacts performance is useful for the patient and the trainee. This should be more easily assessed using the NBA-MAC tool developed by a project supervisor for various scenarios that ACCS trainees encounter during medical emergencies. The ’Nepean-Bell Assessment of the Medical Attitude Categories’ has already been used on anaesthetists to assess their stress and performance in emergent situations, so using a modified tool on ACCS trainees is fitting. Early identification of situations that are too stressful for the trainee and the potential impact on patient care will allow an intervention or cessation of the scenario prior to the trainee being in a situation where they are unable to perform the task. Early interventions for stressful situations or scenarios found to invoke a significant level of stress can be as simple as a debrief, but others may require external assistance in the form of the project supervisor, who is a trusted and experienced fellow clinician, or a referral to a clinical psychologist. These psychological or psychiatric interventions will also apply well to simulated scenarios that imitate real-life situations. In summary, there is much potential for improving the welfare and performance of ACCS trainees involved in medical emergencies through this novel approach. By writing this essay, I hope to gain further knowledge about the psychological and emotional needs of ACCS trainees and what help can be put in place to assist them during emergency situations. This is a beneficial part of the ACCS training and gives trainees experience in a role that they may find themselves in and have to deal with in real medical emergencies. This essay has clearly defined a plan and method for assessing specific scenarios and their impact on the clinician, through to finding the most appropriate form of intervention, which may vary widely depending on the severity of the situation and the effect on the individual. The ultimate goal is to give the clinician the best possible care, which they do for their patients, but in this case, it is improving their own health and psychological wellbeing. (Gill et al.2020)